Preliminary Phytochemical Screening and Anti Bacterial Activity of Leaves of Moringa oleifera. Lamk - Tharshika, S.; Prasad, V.M.; Shivatharsini, R.; Thavaranjit, A.C.; Thayalini, T. (Asian Journal of Medicine and Health, 2017)
Moringa oleifera is a tree belongs to the family Moringaceae. It is called as Drumstick tree in English. In traditional medicine, the leaves and flowers are used in different ways to cure different ailment. Leaf juice is used for the eye infection. Mixed with honey, it is applied as anjanam to the eyelids in eye disease. Antibacterial activity of extracts of seeds, roots and leaves has been reported previously against Escherichia coli, Staphylococcus aureus, Streptococcus pyogenes, Aspergillus niger and Candida albicans. The aim of this study is to screen the Phytochemicals and antibacterial activity of the decoction and ethanolic extract of obtained from the leaves of M.oleifera against Staphylococcus aureus (ATCC 25923), Pseudomonas aeruginosa (ATCC 27853), Escherichia coli (ATCC 25922) and Enterococcus faecalis (ATCC 29212). Fresh leaves were collected from Jaffna, Sri Lanka washed and dried under sunshade for one week. The decoction was prepared using water as solvent, and the ethanol extract was prepared using soxhlet apparatus. These extracts were used to screen the phytochemical and test its antibacterial activity. Both were qualitatively tested for the presence of chemical constituents, such as alkaloids, saponins, tannins, steroids, flavonoids, glycosides and triterpenoids. Antibacterial activity was determined by using the standard well diffusion method. The Nutrient Agar (NA) plate was inoculated with 1 mL (about 1x10⁶ CFU/mL) of each liquid bacterial culture was dispersed on the surface of NA plate and allowed to dry at 37°C for 15 min. The wells with 9 mm in diameter and 4 mm in depth were bored into the NA using a sterile cork borer and the well was completely filled with the test extract. Ethanol alone was used as control. Plates were incubated at 37°C for 24 hrs. Inhibition of growth was observed and the diameters of the zones of inhibition (ZOI) were measured. Replicates were made for the entire procedure. Ethanolic extract of leaf showed antibacterial activity against all tested gram positive and gram negative organisms. ZOI was ranged from 12 ± 0 mm to 19 ± 0 mm. Decoction showed antibacterial activity against S. aureus and E.faecalis the ZOI was 11 ± 0.18 mm. Growth inhibition was highly significant against P. aeruginosa and less significant against E. coli. in ethanol leaf extract. Degree of antibacterial activity of ethanol leaf extract was higher than decoction among the bacteria tested. Saponin, tannin and cardiac glycoside were present in both extract but terpenoid found only in ethanol leaf extract. It was also found that the extraction of bioactive compounds depend on the type of solvent used and the method of extraction. Ethanolic extract of M.oleifera leaf extract exhibited potent antibacterial activity against all tested organisms. It may be due to the presence of terpenoid. It could be used in the treatment of infections caused by these organisms.
Keywords: Phytochemical screening; anti-bacterial activity